Application of Anti-slide Piles in Embankment Reconstruction Work on Soft Soil Foundation - YU Minlin (Renmin Zhujiang)
In order to study the influence of anti-slide pile layout on the anti-slide stability of the embankment reconstruction work on soft soil foundation,taking the Xindian section of Fenghua River embankment in Ningbo as the research object,this paper analyzes the anti-slip stability safety coefficient of the embankment with different length and spacing of anti-slides piles by the finite element software ABAQUS and the strength reduction method.The calculation results show that:The pile in shorter length may not have anti-slide effect yet.When the pile length increases the anti-slide stability safety factor decreases and then tends to be constant with the increase of pile spacing.Under the same pile spacing,the anti-slide stability safety factor of embankment increases and then also tends to be constant with the increase of pile length.Finally,by fitting the curve of anti-slide stability safety coefficient to the pile length and pile spacing,the piles with proper length and spacing are applied in this work.